2019
DOI: 10.1108/mbr-01-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Country-specific determinants of FDI inflows to the MENA region

Abstract: Purpose This paper aims to synthesize, analyze and categorize the empirical literature on country-specific factors that affect foreign direct investment (FDI) inflows to the Middle East and North Africa (MENA) region. Identifying gaps and methodological challenges in the reviewed articles, recommendations are made to guide future research. Design/methodology/approach Applying the systematic review methodology, content analysis is conducted of 42 relevant empirical studies that explore country-specific FDI de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 87 publications
0
17
0
4
Order By: Relevance
“…This is a problem because research has increasingly shown that while managers can and do learn from coping with exogenous shocks, whether political or natural (Oetzel and Oh, 2014;Jiménezet al, 2018), the learning is often constrained to country (Oh and Oetzel, 2017) or even subcountry levels (Oh et al, 2020). This is because countries and sub-regions vary along dimensions of institutional quality, influence of religion, government policy, regulatory enforcement, transparency and business norms (Dimitrova et al, 2019;Estrin and Prevezer, 2011). Indeed, the learning from shocks and subsequent choices may be further constrained or enabled by company-country-specific contingencies such as particular company capabilitiesfor example, country-savvy, in-house legal expertise (White et al, 2020); high-trust relationships with management of other subsidiaries or firms coping with the same uncertainties in the same locations (Oh et al, 2020); and even ideological match between firm and country or regional leadership (Viatcheslav and Tensaout, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a problem because research has increasingly shown that while managers can and do learn from coping with exogenous shocks, whether political or natural (Oetzel and Oh, 2014;Jiménezet al, 2018), the learning is often constrained to country (Oh and Oetzel, 2017) or even subcountry levels (Oh et al, 2020). This is because countries and sub-regions vary along dimensions of institutional quality, influence of religion, government policy, regulatory enforcement, transparency and business norms (Dimitrova et al, 2019;Estrin and Prevezer, 2011). Indeed, the learning from shocks and subsequent choices may be further constrained or enabled by company-country-specific contingencies such as particular company capabilitiesfor example, country-savvy, in-house legal expertise (White et al, 2020); high-trust relationships with management of other subsidiaries or firms coping with the same uncertainties in the same locations (Oh et al, 2020); and even ideological match between firm and country or regional leadership (Viatcheslav and Tensaout, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Independent (moderating) variable -Experience in MENA region. Prior research on both political risk and FDI indicate that experience is domain specific in that only experience in a particular country is useful for understanding and managing risk in that context (Dimitrova et al, 2019;Oh and Oetzel, 2017). Although it proved impossible to capture country-specific relevant experience, we were able to calculate region-specific experience by noting the length of time between 2009 and the date in which the first subsidiary was opened in the MENA region.…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…First, this article seeks to integrate the concept of state fragility in IB research as an important determinant of FDI flows, especially in emerging and developing countries. Second, this paper provides an original analysis of the relationship between state fragility and FDI in a region that remains understudied in IB, namely the MENA region (Dimitrova et al, 2020;Elbanna et al, 2020), by highlighting the importance of location-specific institutional and natural endowment factors likely to moderate this relationship.…”
Section: O T S -C L é S 1 | Introductionmentioning
confidence: 99%
“…Location decisions are crucial for multinational enterprises (MNEs) because they have the potential to determine subsequent company performance (Jain et al , 2013). Correspondingly, a growing body of research has examined different determinants of international location choice (Albino-Pimentel et al , 2018; Cui et al , 2017; Dimitrova et al , 2020; Lu et al , 2014; Schotter and Beamish, 2013). The determinants addressed in the literature can broadly be grouped into firm- and industry-specific determinants, and host country-specific determinants (Jain et al , 2016).…”
Section: Introductionmentioning
confidence: 99%